2011
DOI: 10.3171/2011.2.peds10355
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric patients with poor neurological status and arteriovenous malformation hemorrhage: an outcome analysis

Abstract: Object In general, patients who present with low Glasgow Coma Scale (GCS) scores and/or fixed and dilated pupils are not expected to do well following arteriovenous malformation (AVM) hemorrhage. However, there is a sense among neurosurgeons that pediatric patients may make a better recovery than adults following such an event. There have been few studies focusing on the outcome of pediatric patients with poor neurological status following AVM hemorrhage. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, early surgery was prone to residual lesions due to incomplete preoperative examination and poor intraoperative visual field exposure, the intraoperative DSA in the Hybrid Angio-Surgical suite was recommended to verify complete eradication of the lesion [30]. In addition, the long-term outcomes between these two groups were similar, a contributing factor was probably children's better neural plasticity [31]. Thus, early surgical intervention was recommended for pediatric hemorrhagic AVMs after the initial hemorrhage in this cohort.…”
Section: Timing Of Surgery In Pediatric Hemorrhagic Avmsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, early surgery was prone to residual lesions due to incomplete preoperative examination and poor intraoperative visual field exposure, the intraoperative DSA in the Hybrid Angio-Surgical suite was recommended to verify complete eradication of the lesion [30]. In addition, the long-term outcomes between these two groups were similar, a contributing factor was probably children's better neural plasticity [31]. Thus, early surgical intervention was recommended for pediatric hemorrhagic AVMs after the initial hemorrhage in this cohort.…”
Section: Timing Of Surgery In Pediatric Hemorrhagic Avmsmentioning
confidence: 92%
“…Considering the long potential life span and good neurological plasticity of children [31], the goal of treatment in the pediatric hemorrhagic AVMs must be complete obliteration. Kiri et al reported an obliteration rate of 89% in pediatric patients with low-grade AVMs after microsurgical resection [18].…”
Section: Outcomes Of Pediatric Hemorrhagic Avmsmentioning
confidence: 99%
“…2,16 Interestingly, pediatric patients seem to demonstrate superior outcomes in comparison with adult patients with similar lesions and presentations, although the mechanism underlying these superior outcomes is largely understudied and remains unknown. 21,23 It is important to precisely measure and accurately categorize disability associated with bAVM presentation and treatment to offer families prognosis and informed hopes for neurological recovery. Most series of pediatric bAVM clinical outcomes use the modified Rankin Scale (mRS) to measure disability, despite a lack of validation in pediatric patients.…”
mentioning
confidence: 99%
“…Headache and vomiting are reported in 58-76% of patients and hemiplegia in 16.2 to 62% of patients [4,5,10,[11][12][13]. These clinical signs often reflect the location of the hemorrhage which is supratentorial at 73.4 to 92.85% of reported cases [4,8,14] and in 84.61% of children in our series. These are cerebral vascular malformations, first and foremost the arteriovenous malformations, which are the main causes of HS in children, in a proportion of 42.8 to 46% of cases [9,10].…”
Section: Discussionmentioning
confidence: 86%